Conjunctival melanoma: association of cyclooxygenase-2 tumor expression to prognosis - Proença, Rita Pinto (2018)
PURPOSE: Conjunctival melanoma is a rare but potentially lethal tumor. Its biologic profile is still largely unknown, with recent studies aiming at establishing histopathological and genetic tumor profiles. The aim of this study was to analyze the association between clinicopathological characteristics and tumor expression of cyclooxygenase-2 (COX-2) to prognosis, assessing its usefulness as a possible prognostic marker. METHODS: Case series of 50 patients from 1991 to 2008 with pathologically proven conjunctival melanoma. Demographic, clinical, and pathological characteristics were evaluated by reviewing clinical files and pathology. Expression of COX-2 was studied by immunohistochemistry of formalin-fixed paraffin-embedded tissue samples of 20 melanomas. Samples were classified in a score which included intensity of staining and percentage of cells with positive reactivity. RESULTS: Clinicopathological features significantly associated (p < .05) with a poor prognosis (death) included involvement of fornix and tarsal conjunctiva, tumor thickness exceeding 2 mm, local tumor recurrence, lymph node, and systemic metastasis. In the immunohistochemistry study (n = 20), 18 cases expressed COX-2 although with different scores. However, only cases with a high score were associated with a poor outcome. Multivariate association analysis revealed that recurrence rate, metastasis, corneal invasion, and tumor thickness were associated with high score cases and, therefore, with a clinical profile with a higher risk of death. CONCLUSIONS: Results suggest that higher COX-2 expression may be a negative prognostic factor in conjunctival melanoma. Further studies can address the potential use of anti-COX-2 drugs as adjuvant therapy of this disease.